Compensation of Voltage Sags Due to Short Circuits on Distribution Lines (Feeders) with Dynamic Voltage Restorer (DVR) - Rakhmad Syafutra Lubis; Muhammad Iqbal Nasir Gade; Ramdhan Halid Siregar; Mahdi Syukri; Saifuddin Muhammad Jalil (Yayasan Kawanad, 2026)
Short circuit faults occur frequently on distribution lines. Such faults generate a fault current within a short interval and result in a momentary voltage drop, commonly known as a voltage sag. On a feeder, the short circuits that occur most often are single-phase-to-ground, two-phase, and three-phase faults. To determine the voltage sag on the line caused by a short circuit, it is necessary to analyze the short circuit fault current and voltage sag by assuming the fault point at 25%, 50%, 75%, and 100% of the total length of the BA 15 feeder. The voltage sag when a single-phase-to-ground short circuit occurs at 25%, 50%, 75%, and 100%, respectively, is 8663.68∠0° V, 5773.4∠0° V, 2886.87∠0° V, and 525.48∠0° V. When a two-phase short circuit occurs, the voltage sag is 19022.602∠0° V, 16637.035∠0° V, 12106.47∠0° V, and 11826.98∠0° V, while during a three-phase short circuit it is 5000∠-76.05° V, 10000∠-70.21° V, 15000∠67.05° V, and 18231.99∠24.29° V. This voltage sag disturbance can be corrected using a DVR, which injects the voltage required to restore normal conditions.